Implementation of School Management in Realizing Religious Culture - Khoirun Nisa’; Nabila Anisya (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the religious culture developed and how school management strategies in developing religious culture in MAN 3 Tambakberas Jombang. This research uses a qualitative approach with a qualitative descriptive research type. Data collection techniques in this study using observation, interviews and documentation. The results showed that the religious culture developed in MAN 3 Jombang, namely 2S culture (greetings and salim), reading al-qur'an, praying before and after teaching and learning activities, praying dhuha and praying dzuhur in congregation, cult after dhuha prayer, memorization program, guidance program to read the Koran, protect the environment and celebrate Islamic holidays. Among the management strategies implemented by schools in developing religious culture in MAN 3 Jombang, namely habituation, exemplary, advice and punishment.